ATP-dependent protein kinase-catalyzed phosphorylation of a seryl residue in HPr, a phosphate carrier protein of the phosphotransferase system in Streptococcus pyogenes. - Deutscher, J (1983)
HPr, a phosphate carrier protein of the streptococcal phosphotransferase system, is phosphorylated at the N-1 position of a single histidyl residue in a reaction requiring phosphoenolpyruvate (P-ePrv), Mg2+, and enzyme I (P-ePrv-HPr phosphotransferase, EC2.7.3.9). We demonstrate that in addition to this reaction, a seryl residue within HPr can be phosphorylated in an ATP-dependent process. This reaction is catalyzed by a protein kinase with an approximate Mr of 20,000. In whole cells the kinase activity is stimulated by glucose, whereas in crude extracts the activity is stimulated by glycolytic intermediates such as glucose 6-phosphate, fructose 1,6-diphosphate, and 2-phosphoglycerate. P-(Ser)-HPr cannot transfer its phosphate group via enzyme II to a sugar as does the P-(His)-HPr. Instead, a phosphatase (Mr = 70,000) was found to hydrolyze the phosphate group of P-(Ser)-HPr. The phosphatase reaction is strongly inhibited by the addition of P-ePrv and enzyme I. Protein kinase-catalyzed phosphorylation of the enzyme constituents of the phosphotransferase system in Escherichia coli has also been demonstrated. These observations lead us to suggest that phosphorylation of a seryl residue in HPr is involved in the regulation of sugar transport in the bacteria cell.